Water and forests as instruments for sustainable regional development. (28th August 2007) - Barkin, David; Pailles, Carlos
An inappropriate development programme at a mega-tourist project has dramatically reduced water levels in the underground aquifers at Bahias de Huatulco, a beautiful site on the Pacific coast of Oaxaca, Mexico. The indigenous communities in the neighbouring highlands suffered, as their forests were logged and their identity was threatened by the pressures from the globalised tourist programme. By compensating rural groups for their efforts to protect and rebuild these forests, a watershed rehabilitation programme sponsored by a local NGO, with funds from national and international governments, is beginning to help increase local incomes by stimulating conservation efforts and sustainable management and production practices. These programmes are strengthening communal organisations and creating alternatives to the marginal economic opportunities offered by the beach community. Their improved land and water management techniques are facilitating the recharging of the aquifer and new productive activities include reforestation, a wood products industry for forestry by-products, a pure water bottling plant, ecotourism and the creation of natural reserves.